Leshchinskaya O. A. National expression of the emotion of fear in Russian and Belarusian phraseological units - Leshchinskaya O. A. (Philological Treatises, 2020)
The article singles out the main structural metaphorical patterns of phraseological units expressing the emotion of fear, and explores models common for Belarusian and Russian, as well as those peculiar for each language. It is pointed out that the structural patterns reflect both universal features and peculiarities of perception and reflection of this emotion for each nation.